2018
DOI: 10.14419/ijet.v7i3.28.20959
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Wave Overtopping from Various Geometrical Configurations of Coastal Breakwater Ramps

Abstract: Breakwater is often required for erosion protection. The effectiveness of breakwater structure as a coastal defence could be determined through overtopping wave surpass onto its crest freeboard structure. The common design practice of breakwater structure is using a linear ramp configuration. There is still a limited knowledge on the contribution of various configuration ramps shape into breakwater efficiency. Thus, this study attempts to investigate a few other's configuration of ramp geometries through overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Further study on ramp parameters has been conducted by (Barbosa et al, 2019) which determines that concave and convex shapes are potential parameters for replacing linear shapes. Furthermore, the latest study by (Musa et al, 2018;2021) found that the cubic ramp shape is the best parameter for allowing more overtopping waves to enter the reservoir. In that study, seven polynomial shapes were tested using experimental and simulation approaches under mild wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Further study on ramp parameters has been conducted by (Barbosa et al, 2019) which determines that concave and convex shapes are potential parameters for replacing linear shapes. Furthermore, the latest study by (Musa et al, 2018;2021) found that the cubic ramp shape is the best parameter for allowing more overtopping waves to enter the reservoir. In that study, seven polynomial shapes were tested using experimental and simulation approaches under mild wave conditions.…”
Section: Introductionmentioning
confidence: 99%